Surgical Audit of Common Bile Duct Injury During Laparoscopic Cholecystectomy in Tertiary Care Center - Muhammad Haris, Hazrat Bilal, Abdul Qadoos, Rizwan4, Hadees, Daniyal Zahoor, Mahak (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current study conducted a surgical evaluation of laparoscopic cholecystectomy in a tertiary care hospital. Methods: A descriptive retrospective study was conducted at the department of surgery, JPMC between dates. All cases of patients who were above 18 years, had cholecystitis or cholelithiasis, and underwent cholecystectomy between 1st January 2013 and 31 December 2014 at Jinnah Postgraduate Medical Center were included. Only cases with complete history, examination and investigations were included. Cases with incomplete information were excluded. Sociodemographic information such as age and gender, clinical information related to biliary duct injury (BDI), causes of BDI, and risk factors for BDI were included in the study. Data was entered and analyzed using SPSS version 21. The findings were narrated in tabulated form. Result: A cumulative count of 21 bile duct injuries (BDIs) was documented, leading to an overall occurrence rate of 3.1%. Most patients (76.2% or 16 individuals) had significant injuries that affected the common bile duct (CBD), main biliary confluence, or main bile ducts. A total of 5 patients, accounting for 23.8% of the cases, had modest injuries that specifically impacted the cystic duct or smaller peripheral or Luschka ducts. The cause of the BDI was diagnosed in 71.4% of instances. Inadequate identification of anatomical features associated with the hepatic pedicle, comprising 33.3% of reported cases, was the most frequently cited cause. Subsequently, it was observed that inflammatory alterations in the gallbladder constituted 26.7% of the cases, while anatomical anomalies accounted for 13.3%. Similarly, the inappropriate application of monopolar coagulation was responsible for an additional 13.3% of the cases. Furthermore, undefined technical errors and challenges encountered during intraoperative hemorrhage management were each attributed to 6.7% of the cases. Conclusion: The present study revealed bile duct injury to be a serious and prevalent complication of laparoscopic cholecystectomy in our center. Therefore, further assessment should be taken in order to avoid occurrence of BDI in patients presenting to the public tertiary care hospitals. Keywords: Surgical audit, minimal invasive surgery, laparoscopic cholecystectomy, preoperative complications, postoperative complications, conversion to open cholecystectomy.